2017
DOI: 10.1002/hed.24792
|View full text |Cite
|
Sign up to set email alerts
|

Significance of perineural invasion in locally advanced bucco alveolar complex carcinomas treated with surgery and postoperative radiation ± concurrent chemotherapy

Abstract: Compared with patients with PNI-negative disease, patients with PNI-positive disease had much worse outcome despite aggressive adjuvant treatment. It warrants escalation of therapy and modification in radiation portals to cover neural pathways in patients with PNI-positive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Thirty minutes after SE onset, the tissue content of GABA in all groups was lower than that in the sham group, but the tissue content of GABA in the PV group was significantly higher than that in the sh-PV group. The aforementioned findings indicate an elevation in the tissue content of Glu across all groups during the onset of SE, which is consistent with previous reports that demonstrated a 6-fold increase in Glu tissue content in the hippocampus of patients with epilepsy compared with the control group …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thirty minutes after SE onset, the tissue content of GABA in all groups was lower than that in the sham group, but the tissue content of GABA in the PV group was significantly higher than that in the sh-PV group. The aforementioned findings indicate an elevation in the tissue content of Glu across all groups during the onset of SE, which is consistent with previous reports that demonstrated a 6-fold increase in Glu tissue content in the hippocampus of patients with epilepsy compared with the control group …”
Section: Discussionsupporting
confidence: 92%
“…We found that at SE onset, the levels of PV, GAD65, and GAD67 were increased in the PV group, which was considered to be related to the presence of GluN1 and GluN2B receptors in PV neurons. 40 It has been reported that the level of Glu in the hippocampus of patients with epilepsy is six times higher than that in normal controls 41 and that the level of Glu in brain tissue increases significantly during the acute phase of epilepsy. 42 In the current study, PV levels in the sh-PV group exhibited no significant variance compared with that in the normal group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value or significance of pathologic features has not been specifically focused on T3–4 OSCC in previously reported series 6 10 , 20 , 22 , 23 . Anand et al reported that PNI was an independent adverse risk factor associated with poor locoregional control and survival in stage III-IV bucco-alveolar complex cancers 27 . Jardim et al also reported PNI to be an independent predictor for overall survival and disease-free survival in clinical stage III-IV oral tongue and floor of mouth cancers 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Only studies including oncological outcomes (overall survival, disease-free survival, and local recurrence-free survival) for patients affected by oral cavity carcinoma (OCC) treated with post-operative chemoradiotherapy who showed the presence of minor risk factors were analyzed. Criteria for exclusion are reported in the Supplementary Materials Table S2 [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ,…”
Section: Methodsmentioning
confidence: 99%